Skepticism and Political Constancy: Richard II and the Garden Scene as a "Model of State". Issue 4 (28th September 2016) - Condren, Conal
Abstract: Many readers have taken the garden scene in Richard II and the voice of its Gardener to constitute a relatively straightforward statement of Shakespeare's notions of good government and constancy in political conduct, in stark contrast to the political disorder depicted in the play. I argue, however, that read in the context of the political and moral issues Shakespeare explored, its value or even relevance to his political world is questionable. The choric voice of the Gardener was not necessarily Shakespeare's. The dramatic point may have been to present, without resolving, the dissonance between the Gardener's vision and the imponderables of political conduct lying beyond his tiny realm.